Estrategias de comunicación y su incidencia en el fortalecimiento del desarrollo agrícola de la asociación 18 de marzo del cantón Puebloviejo provincia los Ríos - Macías Valverde, Andrea Lisbeth (2016)
This paper aims to raise communication strategies for the agricultural sector, in this case the Asociación 18 de Marzo del cantón Puebloviejo of the province of Los Ríos, with a previous study demonstrate the importance of implementing them. It is vital to build in the population of this sector´s interest to keep informed and educated create a strengthened partnership which will serve as an example for other sectors of the province. This research was conducted, technical way finding the problem that exists in the sector, its causes and effects in order to design a proposal to boost to improve internal and external communication of the famers association, because the communication is the single most effective method used to exchange ideas, knowledge, with appropriate implementation partners can perform better in their roles. This study serves to provide proposals and solutions for the benefit of 100 partners and 400 people in total who will benefit directly and indirectly with possible solutions to run, in this case receiving training on different subjects where they can discover their strengths and improve their weaknesses, also educate themselves. To reach fruition this project, agreements with the Universidad Técnica de Babahoyo will be made through the School of Social Communication, developing links with the community, also have the support of the Ministerio de Agricultura, Ganadería, Acuacultura y Pesca (MAGAP). And in the near future be trained leaders achieve undertake and develop according to the National Plan for Good Living with a broad vision and mission as a partnership. The aim is to involve the partners in a full training session 96 hours for 3 months where we will have professional and competent trainers who can teach and cultivate good communications in order to develop skills and tools to improve the daily activities of farmers and also in the near future run enterprises, with the proper implementation of this proposal will demonstrate the importance of having and maintaining a well-structured association with an organized image.